Comparative Study of Transcranial Magneto-Acoustic Stimulation and Transcranial Ultrasound Stimulation of Motor Cortex - Wang, Huiqin; Zhou, Xiaoqing; Cui, Dong; Liu, Ruixu; Tan, Ruxin; Wang, Xin; Liu, Zhipeng; Yin, Tao (Frontiers in Behavioral Neuroscience, 2019)
Transcranial ultrasound stimulation (TUS) (f < 1MHz) is a promising approach to non-invasive brain stimulation. Transcranial magneto-acoustic stimulation (TMAS) is a technique of neuromodulation for regulating neuroelectric-activity utilizing a magnetic–acoustic coupling electric field generated by low-intensity ultrasound and magnetic fields. However, both techniques use the physical means of low-intensity ultrasound and can induce the response of the motor cortex. Therefore, it is necessary to distinguish the difference between the two techniques in the regulation of neural activity. This study is the first to quantify the amplitude and response latency of motor cortical electromyography (EMG) in mice induced by TMAS and TUS. The amplitude of EMG (2.73±0.32mV) induced by TMAS was significantly greater than that induced by TUS (2.22±0.33mV), and the EMG response latency induced by TMAS (101.25 ± 88.4ms) was significantly lower than that induced by TUS (181.25 ± 158.4ms). This shows that TMAS can shorten the response time of nerve activity and enhance the neuromodulation effect of TUS on the motor cortex. This provides a theoretical basis for revealing the physiological mechanisms of TMAS and the treatment of neuropsychiatric diseases using it.